2022
DOI: 10.21037/jgo-22-274
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity of gastric cancer: analysis of key pathogenic transcription factors

Abstract: Background: We aimed to screen the key pathogenic transcription factors of gastric cancer and analyzed the correlation between the expression of transcription factors and chemotherapy drugs in gastric cancer.Methods: Gastric cancer RNA sequencing data sets, single nucleotide polymorphism data sets, and corresponding clinical data sets were downloaded from The Cancer Genome Atlas, which is public data.The expression of transcription factors in gastric cancer and normal tissues was analyzed with R software.Pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…As a transcriptional factor, FOXM1 plays multiple roles in tumorigenesis and development, such as promoting cell differentiation and proliferation, facilitating tumor metastasis, and invasion [ 39 ]. In addition, higher FOXM1 expression predicted less response of GC patients to cisplatin [ 40 ]. Consistent with other studies, the mRNA level of FOXM1 is significantly ( p = 0.0105 and p = 0.0013) higher in cisplatin resistant GC cells ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a transcriptional factor, FOXM1 plays multiple roles in tumorigenesis and development, such as promoting cell differentiation and proliferation, facilitating tumor metastasis, and invasion [ 39 ]. In addition, higher FOXM1 expression predicted less response of GC patients to cisplatin [ 40 ]. Consistent with other studies, the mRNA level of FOXM1 is significantly ( p = 0.0105 and p = 0.0013) higher in cisplatin resistant GC cells ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…The function of FOXM1 in determining sensitivity of cancer cells to chemotherapy drugs has also been reported [ 45 ]. In gastric cancer patients, overexpression of FOXM1 was related to cisplatin resistance, and depletion of FOXM1 improved this resistance [ 40 , 46 ]. FOXM1 was found to be up-regulated in cisplatin resistant GC cells, and KIAA1429 depletion significantly decreased FOXM1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MYBL2 maintains normal cell cycle progression and is a risk predictor for gastric cancer. MYBL2 leads to metastatic recrudescence and poor prognosis in prostate cancer patients [29,30]. The same, Zhang et al pointed out that MYBL2 is a key downstream factor that promotes the progression of glioma, and is related to the clinical stage and overall survival of patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high RXRG mRNA expression was signi cantly correlated with better tumour characteristics and longer progression-free survival for breast cancer patients(Joseph et al 2019). It has also been shown that RXRG can improve the prognosis of patients with gastric cancer(Weng et al 2022). GO and KEGG analyses were performed to reveal the function of potential targets in the treatment of NSCLC.…”
mentioning
confidence: 99%